Bureaucracy Neutrality in The Post of The Simultaneous Regional Elections in Karawang Regency in 2024 - Jhodie Faja Agustian; Dede Sri Kartini; Neneng Yani Yuningsih (Universitas Muhammadiyah Gorontalo, 2025)
Indonesia as a country that adheres to a democratic system, of course and will definitely hold general elections every agreed period. In every democratic party (Election or Regional Election), bureaucratic apparatus is often in a dilemma because bureaucratic apparatus are employees who are appointed and dismissed by the Civil Service Development Officer (PPK) who has the status of a political official. This dilemma is also experienced by bureaucratic apparatus in Karawang Regency which is holding a simultaneous regional election process in 2024. This study uses a qualitative method to understand a phenomenon that occurs holistically through words and language descriptively. The data obtained by this study uses several stages, such as observation, interviews, and documentation to obtain the data needed during the research process. This study produces results that bureaucratic neutrality in Karawang Regency is running optimally, which is marked by the commitment, moral integrity, and responsibility that each bureaucratic apparatus has. Other indicators include a professional attitude, no conflict of interest, and compliance with existing regulations that run optimally, which is indicated by the minimal cases of violations of neutrality committed by bureaucratic apparatus. This condition is a result of cooperation between the KPU, Bawaslu, and BKPSDM in Karawang Regency, which routinely carry out various activities and remind bureaucratic apparatus to always be neutral in the process of organizing simultaneous regional elections. This study can produce conclusions that bureaucratic apparatus have commitment, moral integrity, and responsibility, have a sense of professionalism and are impartial, have no conflict of interest, and comply with regulations regarding neutrality during and after simultaneous regional elections in Karawang Regency.